Bradykinin induces interleukin-6 expression in astrocytes through activation of nuclear factor-κB - Schwaninger, Markus; Sallmann, Svea; Petersen, Nicole; Schneider, Armin; Prinz, Simone; Libermann, Towia A.; Spranger, Matthias (Journal of neurochemistry, 1999)
Bradykinin, a mediator of inflammation, is produced in the brain during trauma and stroke. It is thought to open the blood-brain barrier, although the mechanism is unclear. We have investigated, therefore, the effect of bradykinin on the expression of interleukin-6 (IL-6), a putative modulator of the blood-brain barrier, in astrocytes. IL-6 gene transcription was evaluated by transient transfection of the human IL-6 promoter linked to the luciferase gene. In murine astrocytes, bradykinin stimulated IL-6 secretion and gene transcription. The effect of bradykinin was blocked by KN-93, an inhibitor of Ca2+/calmodulin-dependent protein kinases, and by bisindolyl-maleimide I, an inhibitor of protein kinase C, suggesting the involvement of these protein kinases. Mutations in the multiple response element and the binding site for nuclear factor-κB (NF-κB), but not in other known elements of the IL-6 promoter, interfered with induction of IL-6 transcription. The involvement of NF-κB was supported further by the binding that overexpression of nmIκBα, a stable inhibitor of NF-κB, inhibited the induction of IL-6 by bradykinin. Bradykinin activated NF-κB in primary astrocytes as shown by increased DNA binding of NF-κB. These data demonstrate that bradykinin stimulates IL-6 expression through activation of NF-κB, which may explain several inflammatory effects of bradykinin.
Elektronische Reproduktion der Druck-Ausgabe
Gesehen am 01.04.2021